Traditional zootherapeutic studies in India: a review - Jaroli DP; Mahawar Madan (BMC, 2008)
Abstract The present study aims to review the zootherapeutic practices of the different ethnic communities of India. This work is also an attempt to present a list of animals' use for medicinal purposes by different communities of India. Data were gathered from 15 published research papers of various authors on zootherapeutic studies in India from 2000 to 2007. Approximately 109 animals and their 270 uses are reported in traditional medicine in different parts of India. Of these, the highest numbers of animal species (42, 38.5%) with 50 (18.5%) uses have been reported for the treatment of Respiratory system related problems. Rheumatic and other pains are treated with 32 species (29.4%) in 34 (12.9%) uses. Gastric problems are reported to be treated with 22 (20.2%) species in 26 (9.9%) uses. The mammals constitute the highest number of animals used for medicinal purposes. 44 (40%) mammals, 24 (22%) invertebrates, 18 (17%) birds, 12 (11%) reptiles, nine (8%) fishes and two (2%) amphibians have been reported for medicinal purposes. Of the total 109 animal species reported, 76(70%) are included in IUCN red data list and 36 (33%) animal species are listed in CITES appendix I, II, and III. This work will be helpful in biodiversity conservation in India and also give a clue to investigate bio-active compound in these animal raw materials.